Microbial activities and physicochemical properties of coniferous forest soilsin two forest areas (arid and semi-arid) of western Algeria - Mohamed, Zouidi; Habib, Borsali Amine; Ayoub, Allam; Raphael, Gros (BOSQUE, 2019)
The Algerian forest, the last bulwark against desertification coming from Sahel, is particularly vulnerable to global change and must be protected from deforestation, which is constantly advancing. Aleppo pine, which covers 880,000 ha, is the predominant species of forests in semi-arid and arid regions. The soils of these regions are generally fragile and vulnerable due to climatic aridity; their degradation today has accentuated the phenomenon of desertification.The objective of this work was to compare the physicochemical and microbiological characteristics of the coniferous forest soils of the semi-arid and arid zones of the Algerian west. In addition to characterization of climates, 16 physical, chemical and microbiological properties were analyzed on soils collected from forest areas characteristic of the two zones: Jebel Sid Ahmed Zeggai forest massif (Saida province) located in the semi-arid zone and the forest massif of jebel Antar (Naama province) located in the arid zone. Our results showed very different soil qualities between the two zones: moisture content, water retention capacity, permeability, porosity and organic carbon content, total nitrogen and organic matter are higher in the semi-arid zone compared with the arid zone, which is characterized by the large presence of total limestone. Biomass and microbial basal respiration are higher in the semi-arid zone. Our results are discussed with regard to the vulnerability of soils to the respective climate of each of the zones and agro-silvo practices potentially involved in the degradation of these soils.